Density of small dendritic spines and microtubule-associated-protein-2 immunoreactivity in the primary auditory cortex of subjects with schizophrenia - McKinney, Brandon C.; MacDonald, Matthew L.; Newman, Jason T.; Shelton, Micah A.; DeGiosio, Rebecca A.; Kelly, Ryan M.; Fish, Kenneth N.; Sampson, Allan R.; Lewis, David A.; Sweet, Robert A. (Neuropsychopharmacology (New York, N.Y.), 2019)
Previously, we demonstrated that dendritic spine density (DSD) in deep layer 3 of the primary auditory cortex (A1) is lower, due to having fewer small spines, in subjects with schizophrenia (SZ) than non-psychiatric control (NPC) subjects. We also previously demonstrated that microtubule-associated-protein-2 immunoreactivity (MAP2-IR) in A1 deep layer 3 is lower, and positively correlated with DSD, in SZ subjects. Here, we first sought to confirm these findings in an independent cohort of 25 SZ-NPC subject pairs (cohort 1). We used immunohistochemistry and confocal microscopy to measure DSD and MAP2-IR in A1 deep layer 3. Consistent with previous studies, both DSD and MAP2-IR were lower in SZ subjects. We then tested the hypothesis that MAP2-IR mediates the effect of SZ on DSD in a cohort of 45 SZ-NPC subject pairs (combined cohort) that included all subjects from cohort 1 and two previously studied cohorts. Based on the distribution of MAP2-IR values in NPC subjects, we categorized each SZ subject as having either low MAP2-IR (SZ MAP2-IR(low)) or normal MAP2-IR (SZ MAP2-IR(normal)). Among SZ MAP-IR(low) subjects, mean DSD was significantly lower than in NPC subjects. However, mean DSD did not differ between SZ MAP2-IR(normal) and NPC subjects. Moreover, MAP2-IR statistically mediated small spine differences, with lower MAP2-IR values associated with fewer small spines. Our findings confirm that low density of small spines and low MAP2-IR are robust SZ phenotypes and suggest that MAP2-IR mediates the effect of SZ on DSD.